Mycobacterium tuberculosisis the causative agent of tuberculosis in the southern ecological zones of Cameroon, as shown by genetic analysis - Assam, Jean Paul Assam; Beng, Véronique Penlap; Cho-Ngwa, Fidelis; Toukam, Michel; Ngoh, Ane-Anyangwe Irene; Kitavi, Mercy; Nzuki, Inosters; Nyonka, Juliette N; Tata, Emilienne; Tedom, Jean Claude; Skilton, Robert A.; Pellé, Roger; et al. (Springer, 2013)
Tuberculosis (TB) is a major cause of mortality and suffering worldwide, with over 95% of TB deaths occurring in low- and middle-income countries. In recent years, molecular typing methods have been widely used in epidemiological studies to aid the control of TB, but this usage has not been the case with many African countries, including Cameroon. The aims of the present investigation were to identify and evaluate the diversity of the Mycobacterium tuberculosis complex (MTBC) isolates circulating in two ecological zones of Cameroon, seven years after the last studies in the West Region, and after the re-organization of the National TB Control Program (NTBCP). These were expected to shed light also on the transmission of TB in the country. The study was conducted from February to July 2009. During this period, 169 patients with symptomatic disease and with sputum cultures that were positive for MTBC were randomly selected for the study from amongst 964 suspected patients in the savannah mosaic zone (West and North West regions) and the tropical rainforest zone (Central region). After culture and diagnosis, DNA was extracted from each of the MTBC isolates and transported to the BecA-ILRI Hub in Nairobi, Kenya for molecular analysis.Genetic characterization was done by mycobacterial interspersed repetitive unit–variable number tandem repeat typing (MIRU-VNTR) and Spoligotyping.Molecular analysis showed that all TB cases reported in this study were caused by infections with Mycobacterium tuberculosis (98.8%) and Mycobacterium africanum (M. africanum) (1.2%) respectively. We did not detect any M. bovis. Comparative analyses using spoligotyping revealed that the majority of isolates belong to major clades of M. tuberculosis: Haarlem (7.6%), Latin American-Mediterranean (34.4%) and T clade (26.7%); the remaining isolates (31.3%) where distributed among the minor clades. The predominant group of isolates (34.4%) corresponded to spoligotype 61, previously described as the “Cameroon family. Further analysis based on MIRU-VNTR profiles had greater resolving power than spoligotyping and defined additional genotypes in the same spoligotype cluster.The molecular characterization of MTBC strains from humans in two ecological regions of Cameroon has shown that M. tuberculosis sensu stricto is the predominant agent of TB cases in the zones. Three decades ago, TB was reported to be caused by M. africanum in 56.0% of cases. The present findings are consistent with a major shift in the prevalence of M. tuberculosis in Cameroon.